Patient Perspectives on Home Tonometer Usage for Glaucoma - Thaprawat P; Dugan SP; Zhang AD (Clinical Ophthalmology)
Pariyamon Thaprawat,1 Sarah P Dugan,1,2 Amy D Zhang1 1Department of Ophthalmology and Visual Sciences, W. K. Kellogg Eye Center, University of Michigan Medical School, Ann Arbor, MI, USA; 2Department of Ophthalmology, Casey Eye Institute, Oregon Health and Science University, Portland, OR, USACorrespondence: Amy D Zhang, Department of Ophthalmology and Visual Sciences, W. K. Kellogg Eye Center, University of Michigan Medical School, 1000 Wall Street, Room 215 Kellogg Tower, Ann Arbor, MI, 48105, USA, Tel +1 734-615-2479, Fax +1 734-232-0864, Email amydz@med.umich.eduPurpose: To understand patient experiences using the iCare HOME tonometer through assessing ease of use, device usage patterns, proficiency, and patient comments.Methods: We conducted a prospective survey-based cohort study of 19 patients (35 eyes) with glaucoma or glaucoma suspect diagnoses. Patients received training on home tonometer usage and were loaned the device for one week to measure intraocular pressure at home multiple times daily. Participants completed a journal and survey at the end of the study period.Results: On average, participants measured intraocular pressure ≥ 4 times per eye each day (4.19± 1.54 OD and 4.06± 1.41 OS). Most found the home tonometer moderately or very easy to use (75% total, 31% and 44% respectively) and would be happy to use the device in the future (94%). The home tonometer was deemed comfortable to use (94%). Most participants were able to use the device without assistance from another person (88%). Many felt that they became proficient at using the home tonometer (94%) and proficiency was achieved typically by day 3 of usage. Patient comments provided insight into sources of difficulty in usage and motivations for home tonometry.Conclusion: Home tonometry was easy to use and comfortable for most patients with proficiency in usage quickly achieved by day 3. Surveying patient perspectives revealed sources of difficulties in home tonometer usage. Patients were eager to obtain home intraocular pressure measurements that could help with disease management.Keywords: glaucoma, home tonometry, rebound tonometry, ease of use, proficiency